2015
DOI: 10.1111/imm.12480
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced differentiation of intraepithelial lymphocytes in the intestine of polymeric immunoglobulin receptor‐deficient mice

Abstract: Summary To clarify the effect of secretory IgA (sIgA) deficiency on gut homeostasis, we examined intraepithelial lymphocytes (IELs) in the small intestine (SI) of polymeric immunoglobulin receptor‐deficient (pIgR−/−) mice. The pIgR−/− mice exhibited the accumulation of CD8αβ+ T‐cell receptor (TCR)‐αβ+ IELs (CD8αβ+αβ‐IELs) after weaning, but no increase of CD8αβ+γδ‐IELs was detected in pIgR−/− TCR‐β−/− mice compared with pIgR+/+ TCR‐β−/− mice. When 5‐bromo‐2′‐deoxyuridine (BrdU) was given for 14 days, the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The increase in the stool IgG of the pIgR KO mice may also be serving as a protective compensatory mechanism to prevent bacterial translocation. Kato-Nagaoka et al recently confirmed earlier reports of increased bacterial counts from the mLNs of pIgR KO mice, however they detected lower values than previous studies [ 13 , 28 , 31 ]. Several factors, including technical details of the assay and variability in local animal facility microbiomes may account for these differences.…”
Section: Discussionsupporting
confidence: 70%
“…The increase in the stool IgG of the pIgR KO mice may also be serving as a protective compensatory mechanism to prevent bacterial translocation. Kato-Nagaoka et al recently confirmed earlier reports of increased bacterial counts from the mLNs of pIgR KO mice, however they detected lower values than previous studies [ 13 , 28 , 31 ]. Several factors, including technical details of the assay and variability in local animal facility microbiomes may account for these differences.…”
Section: Discussionsupporting
confidence: 70%
“…Despite differences in microbial communities, colonic mucus thickness is similar in pIgR KO mice compare to controls [ 14 ]. Small intestinal mucus thickness has not been directly assessed; however, small intestinal permeability may increase with age in pIgR KO mice compared to controls [ 59 ]. 6.…”
Section: Lessons From Pigr-deficient Micementioning
confidence: 99%
“…Lysozyme and secretory IgA (SIgA), which is composed of two IgA molecules and is transported by pIgR, are two important mucosal immune system effectors. They help prevent infection and remove antigens crossing the mucosal barrier [4] [5]. Our previous study had indicated that cyclophosphamide could induce the expression of lysozyme and sIgA [6].…”
Section: Introductionmentioning
confidence: 99%